2020
DOI: 10.15283/ijsc19073
|View full text |Cite
|
Sign up to set email alerts
|

IL6 Receptor Facilitates Adipogenesis Differentiation of Human Mesenchymal Stem Cells through Activating P38 Pathway

Abstract: Background and Objectives: Mesenchymal stem cells (MSCs) have the multipotent capacity to differentiate into multiple tissue lineages as well as to self-renew, which is the main origin of adipocytes. IL6/IL6R pathway exerts a significant role in tissue regeneration and cell differentiation. Whereas, the underlying mechanism between IL6/IL6R pathway and MSCs adipogenesis differentiation remains elusive. Methods: MSCs from healthy donors were cultured in adipogenesis differentiation medium for 0∼14 days, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…Owing to the opposing roles described for the MAPK pathway, one hypothesis states that the activation of MAPK can have different effects depending on the stage of differentiation. This hypothesis is in agreement with the fact that the differentiation process of 3 T3-L1 adipocytes requires a specific proliferative step (called mitotic clonal expansion, MCE) at the beginning [38,40]. In addition, p38 MAPK activity was significantly higher in preadipocytes than in adipocytes [39], again suggesting that p38 MAPK activity has to be regulated in a timely manner during adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 83%
“…Owing to the opposing roles described for the MAPK pathway, one hypothesis states that the activation of MAPK can have different effects depending on the stage of differentiation. This hypothesis is in agreement with the fact that the differentiation process of 3 T3-L1 adipocytes requires a specific proliferative step (called mitotic clonal expansion, MCE) at the beginning [38,40]. In addition, p38 MAPK activity was significantly higher in preadipocytes than in adipocytes [39], again suggesting that p38 MAPK activity has to be regulated in a timely manner during adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the results of this study indicate that the MAPK signaling pathway may be important for mediating subcutaneous adipogenesis in Jiaxing Black pigs. Considering that ERK and p38 are two main kinases in the MAPK pathway, and opposite results were observed for the regulatory functions of ERK and p38 during adipocyte differentiation [35][36][37], we further compared the activation of p38/ERK in subcutaneous adipose tissue of the two pig breeds. We found that there was practically no p38 phosphorylation in LW pigs, which contrasted with high abundance of phosphorylated p38 in JX pig adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, ALP levels and calcium nodule formation were both suppressed by p38 silencing (Figure 6E [28]. The ability of MSCs to differentiate into multiple lineages is controlled by various inhibitors and stimulators, which have been studied by in vivo or in vitro [29,30]. Enhanced MSCs osteogenic differentiation can be achieved by various methods, such as electrical stimulation, chemical supplements, and co-culturing with assisting cells [31,32].…”
Section: The Effects Of P38 Sirna On the Osteogenic Differentiation Omentioning
confidence: 76%